(untitled) (Italian Journal of Public Health, 2011)
Background: Immigrant children represent the fastest-growing segment of the child population in Italy and an increasing proportion of patients attending the daily practices of paediatricians. The aim of this survey was to investigate the health status of migrant children in Italy and, based on the perceptions of paediatricians, to identify the healthcare needs of this segment of immigrant patients. Methods: The survey was carried out between October 2006 and September 2007 on a sample of Italian paediatricians. Results: The sample included 236 paediatricians, accounting for 190,335 paediatric patients in total; of these, 14,308 (7.5%) were immigrant children. The rates of access to recommended vaccinations of immigrant children compared to national data were as follows: Pertussis (87.9% of sample vs 96.7% National data), Haemophilus influenzae (86.5% vs 96%) and Measles, Mumps and Rubella (MMR) (87.3% vs 89.6%). We also found differences in caesarean birth rate (11.8% of immigrant births being caesarean compared to national data, that reaches about 38.3%) and a high rate of parasitosis in immigrant children. Discussion: The results indicate interesting differences between immigrant and Italian children, especially in vaccination coverage and caesarean birth rate, that further studies could clarify in the future.